Targeted SARS-CoV-2 treatment is associated with decreased mortality in immunocompromised patients with COVID-19. (25th July 2022) - Lafont, Emmanuel; Pere, Hélène; Lebeaux, David; Cheminet, Geoffrey; Thervet, Eric; Guillemain, Romain; Flahault, Adrien
Abstract: Background: Little is known about targeted (antiviral or monoclonal antibody) anti-SARS-CoV-2 treatment in immunocompromised patients with COVID-19. Objectives: To assess the real-life efficacy and tolerance of targeted treatment of COVID-19 in immunocompromised patients. Patients and methods: Single-centre retrospective case series of immunocompromised patients with COVID-19 between December 2021 and March 2022. We recorded all cases of COVID-19 among immunocompromised patients treatment between 20 December 2021 and 15 March 2022. Choice of treatment was left to the physician's decision, according to internal treatment protocol, treatment availability and circulating variants. Main outcome was death from COVID-19 after no treatment or targeted treatment. Results: Sixty-seven immunocompromised patients [38 male; median (IQR) age, 53 (43–63) years], with a median (IQR) follow-up of 60 (47–80) days. Ten patients did not receive any targeted treatment. Targeted treatment consisted of IV curative remdesivir ( n = 22), sotrovimab ( n = 16), tixagevimab/cilgavimab ( n = 13) and casirivimab/imdevimab ( n = 1). Ten patients (15%) presented severe COVID-19 and 2 (3%) died from Omicron COVID-19. Comparing patients who received targeted anti-SARS-CoV-2 treatment and no prophylaxis, ( n = 42; 81%) with those who did not ( n = 10; 19%), death rate was significantly lower in treated patients [ n = 0 (0%) versus n = 2 (20%); P = 0.034]. No severe adverse events were reported among treated patients. Among 15 patients who received tixagevimab/cilgavimab as pre-exposure prophylaxis, 6 received an additional curative treatment and none died from COVID-19. Conclusions: Our results suggest that targeted COVID-19 treatment, including direct antivirals or monoclonal antibodies, is safe and efficient and could be proposed in high-risk immunocompromised patients.